Left ventricular speckle tracking echocardiographic evaluation before and after TAVI - Vasiliki Tsampasian (Echo Research and Practice, 2020)
Aims: To assess left ventricular (LV) function before and after transcatheter aortic valve implantation (TAVI) using conventional echocardiographic parameters and global longitudinal LV strain (GLS) and compare outcomes between Edwards S3 and Evolut R valves. Methods and results: Data were collected for consecutive patients undergoing TAVI at Hammersmith hospital between 2015 and 2018. Of the 303 patients, those with coronary artery disease and atrial fibrillation were excluded leading to a total of 85 patients, which constituted our study group. The mean follow-up was 49 ± 39 days. In total, 60% of patients were treated with Edwards S3 and 40% Evolut R. TAVI resulted in an early improvement of GLS (−13.96 to −15.25%, P = 0.01) but not ejection fraction (EF) (47.6 to 50.1%, P = 0.09). LV mass also improved, especially in patients with marked baseline LV hypertrophy (P < 0.001). There were no appreciable differences of LV function improvement and overall LV remodelling after TAVI between the two types of valves used (P = 0.14). Conclusions: TAVI results in reverse remodelling and improvement of GLS, especially in patients with impaired baseline LV function. There were no differences in the extent of LV function improvement between Edwards S3 and Evolut R valves but there was a greater incidence of aortic regurgitation with Evolut R.